Orientation and Optical Polarized Spectra (380–900 nm) of Methylene Blue Crystals on a Glass Surface. (23rd July 2013) - Milošević, Maja D.; Logar, M. Mihovil; Poharc-Logar, A. Vesna; Jakšić, N. Ljiljana
Abstract : The crystallographic directions of the crystal toward the vector of polarized light can accurately be positioned, so the information that we gain from polarized spectra can be consistently interpreted according to known crystal structure. The orientation and optical properties of the methylene blue (MB) crystals were analyzed by XRD, XRPD, and polarized VIS-NIR spectroscopy. Cationic dye, MB, was polymerized into crystals on a glass slate. The blue color crystals showed pronounced dichroism, twin lamellar structure and bladed to fibrous habit. According to XRD data, [010] direction lies perpendicular to the crystal surface, so we recognized it as (0k0) face, while [100] and [001] directions coincide with crystal elongation and crystal thickness respectively. In this paper, the polarized spectra of MB crystal are presented, measured with the aim of acquisition of referent values, which could be helpful for the identification of MB molecular aggregation.